Analisis Kesenjangan Keuntungan Usaha Bunga Krisan Di Show Window Dan Di Tingkat Petani Kelurahan Kakaskasen II, Kec. Tomohon Utara Kota Tomohon - Debora Hana Lolowang; Jane Sulinda Tambas; Nordy Fritsgerald Lucky Waney (AGRI-SOSIOEKONOMI, 2022)
This research aims to analyze the profit gap of chrysanthemum business in “Show Window” Land and Farmers' Land in Kakaskasen II Village, North Tomohon District, Tomohon City. This research was conducted from December to April 2022. The selection of respondents was done intentionally. The data collection method is a survey method. Interview data collection techniques using a questionnaire. The data used are primary data and secondary data. Primary data were collected through interviews based on questionnaires, to four farmers. Secondary data were obtained from related institutions, namely the Head of the Show Window Center and the Kelurahan Office. The results showed that the profit of the chrysanthemum flower business in the Show Window area was greater than that of the farmer, namely Rp. 13,635,049, while in the Farmer's Land, it was Rp. 7,705.822. The value of the gap in the profit of chrysanthemum business between the potential performance in the Show Window Land and the actual performance in the Farmer's Land is Rp. 5,891,726. The profit gap that occurs is caused by the cost factor incurred and the resulting revenue factor. Costs that can affect fixed costs are depreciation costs, and variable costs consisting of medicine costs, labor costs, and other costs (electricity and water). Costs that can affect fixed costs are depreciation costs, and variable costs consisting of medicine costs, labor costs, and other costs (electricity and water). Acceptance at the Show Window is greater than that of farmers because production is influenced by land use, chrysanthemum production, cultivation methods, and competent workers.